Rational Design and Fabrication of Biomimetic Hierarchical Scaffolds With Bone-Matchable Strength for Bone Regeneration - Lian, Ruixian; Xie, Peng; Xiao, Lan; Iqbal, Zoya; Zhang, Shihao; Kohn, Joachim; Qu, Xue; Liu, Changsheng; Li, Yulin (Frontiers in Materials, 2021)
The development of scaffolds with bone-mimicking compositions, hierarchical structure, and bone-matchable mechanical properties may offer a novel route for the achievement of effective bone regeneration. Although bioactive glasses have been widely utilized for bone regeneration at the clinical level, their brittleness and uncontrolled pore structure limit further applications. Herein, this study aims to develop a kind of bioactive scaffold with a macroporous/microporous/mesoporous structure via impregnating a sponge template with mesoporous bioactive glass (MBG) sol, followed by sponge template removal. In order to improve the mechanical properties and stability of the MBG scaffolds, desaminotyrosyl ethyl tyrosine polycarbonates (PDTEC), a biodegradable polymer which does not induce acid side-effects caused by conventional polylactide, was selected to decorate the resulting hierarchical scaffolds through a surface coating approach. The PDTEC functionalization endowed the scaffolds with improved mechanical strength matching the bearable range of trabecular bone (2–12 MPa). Meanwhile, the relative neutral pH value was maintained during their degradation process. In vitro studies demonstrated that the PDTEC accelerated the biomineralization of the scaffolds, and promoted the attachment and proliferation, holding high promise for bone regeneration.